Uso do Wordwall como estratégia avaliativa no ensino de Química: uma experiência didática no Ensino Médio em Igarapé-Açú-PA - SANTOS, Ingrid Santos dos (2024)
The present work presents results of an educational research whose objective was to analyze the learning of students of the 2nd year of high school in a State School using as a resource a gamified activity, developed on the Wordwall platform to fix the content of chemical kinetics. The structuring of the didactic strategy consisted of two stages. In the first, the content Chemical Kinetics was presented in a dialogic manner, highlighting the conceptual aspects with everyday examples of the determining factors in the speed of reactions. In the second stage, the gamified activity of Wordwall was used to verify if the students were able to assimilate the subject. To correlate possible learning advances, a questionnaire was applied to probe students' prior knowledge. Therefore, when analyzing the results, a satisfactory percentage of 50% of learning in relation to the content was evidenced. In addition, it is possible to argue that digital platforms that use gamification are essential in classes to diversify the process of teaching and reviewing learning, as in addition to arousing students' interest, they facilitated the identification of learning instantly. In the future, new investigations and tests to deepen the consolidation of longterm learning, as well as interviews about specific difficulties in answering/resolving the questions/challenges proposed by the application.